Role of Kaayam in Postnatal care in Traditional and scientific approach - Nithyapriya, S.; Sivashanmugarajah, S. (Charithra Malika Kerala Historical And Educational Cultural Research Museum,Amaravila, Thiruvananthapuram, 2024)
Postnatal period or postpartum period is the period soon after the delivery of the baby and usually last six to eight weeks. During this period mother become anatomically, physiologically and psychologically return to the pre-pregnant state. Postnatal care is very essential, because it is a critical time for both mother and baby facing many problems. There are some traditional practices that has been followed by the Tamil speaking people in the Northern part of Sri Lanka for the wellbeing of the mother and baby. Taking of Kayam during this period is still in practice. It has potential benefits to mother and baby such as strengthen the uterus and pelvic joints, promote the excretion of wastage like lochia, cell debris and membrane after delivery, increase the appetite and boost the immunity to the mother and it will also boost the functions of mammary gland and promote milk secretion. The aim of the study is to identify the various methods of Kaayamwhich used in Sri Lanka, Organoleptic characters and most specific pharmacological actions of ingredients of Kaayam. The data were collected from Tamil traditions, various Siddha Textbooks, journals and other published sources from August 2023 to October 2023. The preliminary step was taken to provide documentary evidence for the therapeutic effects of the ingredients which are used in the preparation of Kaayam. According to the study, four methods of kaayam were identified. Among them 86% (6) of ingredients has pungent division and 57% (4) of ingredients has hot potency. It makes sure correct and clean channels and most of ingredients has carminative, stimulant, stomachic and diuretic action. Therefore it can manage the digestive problems, genito urinary problems and it boosts the functions of mammary gland and promotes milk secretion. This study concisely summarizes medico therapeutic information concerning kaayam used during postnatal period. This traditional claims wait further pharmacological and biochemical confirmation to prove its efficacies and safety.
Keywords: Postnatal; Kaayam; Traditional; Siddha texts; Pharmacological